INOVASI TEKNIK PEMBELAJARAN PENDIDIKAN AGAMA ISLAM PADA SMA MODEL NEGERI 3 PALU - Halik, Abdul (State Institut of Islamic Studies (IAIN) Palu, 2013)
Abstract. This paper is related to innovation learning Islamic education in the State High School Model 3 Palu. The problem studied is how the shape of the learning technique innovation? How its effectiveness? And how students respond to learning techniques such innovation? The results showed: the form of technical innovation of Islamic education in SMA Negeri 3 Palu models include: development of methods and inquiri diskoveri. Effectiveness of technical innovation makes the subject matter became more understood by learners, because the material was found alone and practiced by the students, while the response of students to technical innovation of Islamic Education is very good and positive, as it can deliver educators to find their own subject matter.Kata kunci: inovasi, teknik, efektivitas, respon, ingkuiri, diskoveri